Analisis Studi Kelayakan Unit Usaha Foto Copy pada Badan Usaha Milik Desa (BUMDes) Agrapana Abadi di Desa Bulian Baru - Siti Marina AZ; Ratna Ratna; Siti Maisarah (Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the Feasibility of Photocopying Business Unit Investment in Agrapana Abadi Village Owned Enterprises (BUM Desa) in Bulian Baru Village. The data analysis method used is descriptive analysis using qualitative data measurements to measure business feasibility and quantitative data measurements through the calculation of investment criteria to measure business feasibility. The amount of investment and working capital of the BUMDes Agrapana Abadi Photo Copy Business Unit is Rp.112,000,000,-;consisting of Rp. 72,000,000,- own capital and capital from banking financial institutions of Rp.40,000,000,- with an interest rate of 12% per year. The conditions of business feasibility aspects which include legal, market and marketing aspects, management and organizational aspects, technical and operational aspects, economic and social aspects, environmental aspects, and financial aspects are feasible to run. The results of the investment feasibility analysis based on the investment criteria which include the calculation of a positive NPV of Rp. 22,461,218.14,- > 0; IRR results are 21.43% > from a SOCC value of 12%; Gross B/C results are 1.033244006 > 1; Net B/C is obtained results 1.311961363 > 1; the Profitability Ratio (PR) results are 1.880803545 > 1 then based on the calculation of business investment criteria more than the standard calculation so it is Feasible to Run. Based on the Return on Investment which includes the Pay Back Period Calculation, the result is 4 Years 5 Months 2 Days < than 5 Years, Break Event Points obtained results are 4 Years 10 Months 3 Days < than 5 Years. So based on the Calculation of Return on Business Investment less than the payback period, the business is Feasible to Run.